2021
DOI: 10.48146/odusobiad.727647
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal Ağ Kullanımının Akıllı Telefon Yoksunluğu Korkusu (Nomofobi) İle İlişkisi: Üniversite Öğrencileri Üzerine Bir Araştırma

Abstract: Akıllı telefonların fiziksel ve konumsal kısıtlamalar olmadan her zaman ve her yerde erişebilir olması ve aşırı kullanımı, bireyin mobil cihazına erişemediğinde yaşadığı endişeyi ifade eden nomofobi sorunun ortaya çıkmasına neden olmuştur. Akıllı telefonların aşırı kullanımında sosyal ağ sitelerinin etkisi göz önünde bulundurulduğunda, nomofobinin gelişimden sosyal ağ sitelerinin rolünün olup olmamasının sorulması önemli hale gelmektedir. Bu kapsamda, sosyal ağ kullanım alışkanlıklarının nomofobi ile olan iliş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
0
0
1
Order By: Relevance
“…It was concluded that "initiating communication" as a social media usage pattern had a significant positive effect on "device deprivation" and "inability to be online" as nomophobic factors. Dasgupta, Bhattacherjee, Dasgupta, Mukherjee, and Biswas (2017), Taşhan andÜnver (2021), andDiker andUçar (2016) found that social media platforms were mainly used for tasks such as homework, research and information acquisition, finding subject-related materials, collaboration, sharing, and chatting. This suggests a link between the purposes of social media usage and aspects of the "Nomophobia Scale" such as "inability to access information," "inability to be online," and "fear of losing communication."…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that "initiating communication" as a social media usage pattern had a significant positive effect on "device deprivation" and "inability to be online" as nomophobic factors. Dasgupta, Bhattacherjee, Dasgupta, Mukherjee, and Biswas (2017), Taşhan andÜnver (2021), andDiker andUçar (2016) found that social media platforms were mainly used for tasks such as homework, research and information acquisition, finding subject-related materials, collaboration, sharing, and chatting. This suggests a link between the purposes of social media usage and aspects of the "Nomophobia Scale" such as "inability to access information," "inability to be online," and "fear of losing communication."…”
Section: Discussionmentioning
confidence: 99%
“…hipotezinin kabul edilmesi, bazı araştırmalarda ortaya koyulduğu üzere akıllı telefonlarını sosyal mecralarla bağlantı kurmak ve çevrimiçi alışveriş yapmak amacıyla kullananların diğer katılımcılara göre daha yüksek düzeyde nomofobik olabilmeleri açıklanabilir. Bu bulgular, literatürdeki diğer benzer çalışmaların (Işık ve Kaptangil, 2018;Karatay, 2018;Sırakaya, 2018;Gürdin, 2019;Yanılmaz, 2019;Kadıoğlu ve Koşar, 2019;Taşhan ve Ünver, 2021) sonuçlarını destekler niteliktedir. "H5: Nomofobik eğilimler (nomofobi) ile kompulsif çevrimiçi satın alma davranışı arasında anlamlı bir ilişki vardır."…”
Section: Sonuç Ve Tartişmaunclassified